(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
This article discusses the development of scientific proposals and practical recommendations aimed at increasing the efficiency of mechanisms for implementing innovation policy in Uzbekistan, financing innovation activities mainly from the state budget and, unfortunately, a very low share of the private sector. In world practice, for the private sector this is 64.1-74.7%, in this regard, much attention is paid here to improving the efficiency of innovative development of the country’s economy. And also studied the methods and tools for the development of mechanisms for the implementation of innovative activities in the country